PEMANFAATAN KAIN PERCA BATIK YANG MELIMPAH DAN TERABAIKAN SEBAGAI BAHAN PEMBUATAN BROS PETIK (PERCA BATIK) DI DESA PAWEDEN, KECAMATAN BUARAN, KABUPATEN PEKALONGAN - Risqiana, Eky (Program Kreativitas Mahasiswa - Pengabdian Kepada Masyarakat, 2013)
One of the famous town with a batik in Pekalongan is a sub-district of Buaran because almost every village and neighborhood have a business batik work. The tailors of the mothers, young people who did not continue his studies. Much of the rest of the batik cloth dumped and burned. Batik patchwork making alternatives more useful is to make such as batik patchwork accessories. Accessories are still warm with the communities is the veil, accessories namely âbrosâ. In addition to having a high value, batik scarf brooch from has not been seen in public, especially that resulting from a patchwork of batik. So it can be made into one of the variants of products batik that are of interest to the community.